Closed Production Process in the Crumb Rubber SIR Industry - Kartika, Hayu; Wahyuni, Nuraida (Faculty of Science and Technology University of Pramita Indonesia, 2024)
This article explores the Crumb rubber SIR industry in Indonesia, a major export commodity that is also a significant source of environmental pollution. The background of this article is an effort to reduce the environmental impact of the Crumb Rubber SIR production process, which produces liquid and solid waste and requires high energy consumption. This study aims to identify and analyze critical aspects of the production process that contribute to environmental and energy efficiency problems. The mass balance method is used to analyze mass and energy balance in the production process. This paper examines in detail each stage of production, identifies areas where waste is generated, and measures energy consumption at each stage. The results of the study show that there are several critical points in the production process that are responsible for the production of waste and high energy consumption. This analysis helps in suggesting several process and waste management improvements to reduce environmental impact. The results of this study emphasize the need for improvements in SIR Crumb Rubber production methods to reduce and utilize waste. The energy potential that can be utilized in the closed production process in producing crumb rubber is producing biogas as an energy fuel of 56.37 KwH which is obtained from processing 1 ton of rubber raw materials into crumb rubber. This article contributes knowledge to crumb rubber producers in implementing sustainable production operational practices.